Muscle Imbalances and Their Role in Musculoskeletal Injury Risk in Physically Active Individuals: A narrative review - Dobosz, Adam; Wojnowski, Antoni; Domińczak, Jan; Oliwia Bartkowska,; Banatkiewicz, Joanna; Deka, Emilia; Czarnecka, Sofia; Łuczyńska, Gabriela; Babik, Karolina; Bojanowska, Hanna (Journal of Education, Health and Sport, 2026)
Introduction and Purpose: Muscle imbalances, particularly bilateral strength asymmetries and functional strength ratio deficits, are increasingly recognized as modifiable intrinsic risk factors for musculoskeletal injuries in physically active populations. This narrative review aims to synthesize current evidence on the definitions, mechanisms, assessment methods, and clinical implications of muscle imbalances regarding injury risk among athletes. Brief description of state of knowledge: Prospective studies indicate that bilateral strength asymmetries exceeding 10–15% are consistently associated with elevated injury risk, although specific thresholds depend on the muscle group and assessment method. Isokinetic dynamometry and force plate assessments are commonly employed for quantification. Evidence links quadriceps asymmetry, hamstring weakness, and adductor deficits to knee, hamstring, and groin injuries, respectively. Sport-specific demands significantly influence asymmetry profiles. Prevention strategies, such as targeted resistance training and neuromuscular interventions, are effective in reducing asymmetries. Summary (Conclusions): Muscle imbalances are critical risk factors requiring targeted intervention when exceeding sport-specific thresholds. Screening programs should utilize validated tools appropriate to the context. Future research must focus on methodological standardization and longitudinal studies. Clinicians are advised to implement individualized screening and corrective strategies within injury prevention frameworks.